Conventional versus Modified Preauricular Incision Approaches to the Management of Temporomandibular Joint Ankylosis in Sanaa City, Yemen: A Comparative Clinical Study - Al-Hudaid, Ali; Hussien, Mohammed; Al-Wesabi, Mohammed; Aldialami, Abdullwahab; Helmi, Jameel (University of Science and Technology, Yemen, 2017)
Objective To compare between the conventional and modified preauricular incision approaches to the management of temporomandibular joint (TMJ) ankylosis among Yemeni patients in Sanaa city, Yemen. Methods This comparative clinical study recruited ten patients (7 males and 3 females; age range: 635 years) with true fully or partially bony or fibrous TMJ ankylosis. These patients were admitted to and followed up in the Department of Oral and Maxillofacial Surgery, College of Dentistry, University of Science and Technology Hospital in Sanaa in the period from May 2013 to February 2016. Five patients with condylar capsule ankylosis were subjected to the conventional preauricular approach, while the other five cases with ankylosis that extends beyond the condylar capsule and reaches the zygomatic arch were subjected to the modified preauricular approach. Both approaches were evaluated and compared for the time required, intra- and post-operative complications and aesthetic results. Results The mean times required to carry out the operations were 4.45 and 3.20 hours for conventional and modified preauricular approaches, respectively.Facial nerve injury was present in two patients undergoing the conventional preauricular approach, but this reversed to normal after four to five months. Patient of both groups experienced no facial paralysis or post-operative auriculotemporal syndrome. Intra-operative bleeding was mild to moderate among the patients of both approaches, and none of the patients required blood transfusion intra- or post-operatively. Major blood vessels were injured in three cases undergoing the conventional preauricular approach. All patients subjected to both approaches showed satisfactory aesthetic end results. Conclusions Conventional and modified preauricular approaches provide excellent accessibility and visibility to the surgical field during the management of TMJ ankylosis among Yemeni patients, with the latter being slightly superior. In addition, the modified preauricular approach is associated with fewer complications, absence of facial nerve injury and reduced surgical time compared to the conventional approach.